Evaluation of The Sports Special Class Implementation Program of Junior High School Level in Sleman District - Kusuma, Addy Idris; Suherman, Wawan Sundawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this research was: (1) to find out the results of the Context evaluation of the Sports Special Class (KKO) program, (2) to find out the results of the Input evaluation of the Sports Special Class (KKO) program, (3) to find out the results of the Process evaluation of the Sports Special Class Program (KKO), and (4) to find out the results of the Product evaluation of the Sports Special Class (KKO) program at the junior high school level in Sleman Regency. This research is evaluation research, using a quantitative approach by considering the CIPP model (context, input, process, product) evaluation in the Sports Special Class (KKO) program at the junior high school level in Sleman Regency. This research was implemented from April to May 2019. The subjects in this research were the Principal, Deputy Principal, Coordinator of KKO implementation, and the students from the three schools. The data of this research were obtained from interviews and questionnaires. The data analysis technique used in this research is descriptive analysis supported by quantitative data. The results of this research are (1) the overall context variable is good, (2) the overall input variables are included in the sufficient category, (3) the overall process variable is in the sufficient category. The obstacle is the arrangement of practice schedules and other lesson schedules so they don’t interfere with each other. And (4) the overall product variable is good. This is proved by the KKO program’s students who have good sports achievements can become champions at the national level and their academic achievements are also with an average report card score of no less than 75.